Positive Solutions for Boundary Value Problems of N-Dimension Nonlinear Fractional Differential System. (5th January 2009) - Yang, Aijun; Ge, Weigao
Abstract : We study the boundary value problem for a kindN -dimension nonlinear fractional differential system with the nonlinear terms involved in the fractional derivative explicitly. The fractional differential operator here is the standard Riemann-Liouville differentiation. By means of fixed point theorems, the existence and multiplicity results of positive solutions are received. Furthermore, two examples given here illustrate that the results are almost sharp.